A randomized prospective study comparing mobile-bearing against fixed-bearing PFC Sigma cruciate-retaining total knee arthroplasties with ten-year minimum follow-up. (October 2018) - Powell, A. J.; Crua, E.; Chong, B. C.; Gordon, R.; McAuslan, A.; Pitto, R. P.; Clatworthy, M. G.
Abstract : Aims: This study compares the PFC total knee arthroplasty (TKA) system in a prospective randomized control trial (RCT) of the mobile-bearing rotating-platform (RP) TKA against the fixed-bearing (FB) TKA. This is the largest RCT with the longest follow-up where cruciate-retaining PFC total knee arthroplasties are compared in a non-bilateral TKA study. Patients and Methods: A total of 167 patients (190 knees with 23 bilateral cases), were recruited prospectively and randomly assigned, with 91 knees receiving the RP and 99 knees receiving FB. The mean age was 65.5 years (48 to 82), the mean body mass index (BMI) was 29.7 kg/m 2 (20 to 52) and 73 patients were female. The Knee Society Score (KSS), Knee Society Functional Score (KSFS), Oxford Knee Score (OKS), Western Ontario and McMaster Universities Arthritis Index (WOMAC), and 12-Item Short-Form Health Survey Physical and Mental Component Scores (SF-12 PCS, SF-12 MCS) were gathered and recorded preoperatively, at five-years' follow-up, and at ten years' follow-up. Additionally, Knee Injury and Osteoarthritis Outcome Scores (KOOS) were collected at five- and ten-year follow-ups. The prevalence of radiolucent lines (RL) on radiographs and implant survival were recorded at five- and ten-year follow-ups. Results: At the ten-year follow-up, the RP group (n = 39) had a statistically significant superior score in the OKS (p = 0.001), WOMAC (p = 0.023), SF-12 PCS (p = 0.019), KOOS Activities of Daily Living (ADL) (p = 0.010), and KOOS Sport and Recreation (Sport/Rec) (p = 0.006) compared with the FB group (n = 46). The OKS, SF-12 PCS, and KOOS Sport/Rec at ten years had mean scores above the minimal clinically important difference (MCID) threshold. There was no significant difference in prevalence of radiolucency between groups at five-years' follow-up (p = 0.449), nor at ten-years' follow-up (p = 0.08). Implant survival rate at 14 years postoperative was 95.2 (95% CI 90.7 to 99.8) and 94.7 (95% CI 86.8 to 100.0) for the RP and FB TKAs, respectively. Conclusion: At ten-year follow-up, the mobile-bearing knee joint arthroplasty had statistically and clinically relevant superior OKS, SF-12 PCS, and KOOS (Sport/Rec) than the fixed-bearing platform. No difference was seen in prevalence of radiolucent lines. There was a greater than 94% implant survival rate for both cohorts at 14 years. Cite this article: Bone Joint J 2018;100-B:1336–44.